Acquired von Willebrand syndrome (AVWS) type 2, characterized by decreased high molecular weight multimers, is common in children with severe pulmonary hypertension (PH) - Wieland, Ivonne; Diekmann, Franziska; Carlens, Julia; Hinze, Laura; Lambeck, Katharina; Jack, Thomas; Hansmann, Georg (Frontiers in Pediatrics, 2022)
Background and Objectives: Emerging evidence suggests that increased degradation of von Willebrand factor and decrease in high molecular weight multimers occurs in patients with pulmonary hypertension (PH). However, the link between acquired von Willebrand Syndrome (AVWS) type 2 and PH remains poorly understood. Methods: We retrospectively evaluated the charts of 20 children with PH who underwent bilateral lung transplantation (LuTx) between 2013 and 2022. Von Willebrand variables were determined in 14 of these patients, only 11 patients had complete diagnostics confirmed by multimer analysis. Results: We confirmed AVWS in 82% of the children studied (9 of 11 patients by multimer analysis). The two remaining patients had suspected AVWS type 2 because of a VWF:Ac/VWF:Ag ratio of <0.7. Platelet dysfunction and suspicion of VWS type 1 were diagnosed in one patient each. All but one of the 14 children with severe PH studied had a coagulation disorder. Most patients (9 proven, 2 suspected) had AVWS type 2. Despite a VWF:Ac/VWF:Ag ratio > 0.7, 60% of these patients suffered from AVWS type 2. In the group of patients with VWS, 33% suffered from hemostatic complications. By contrast, the rate of complications was higher (67%) in the group without diagnostics and therapy. Conclusion: Therefore, for children with moderate to severe PH, we recommend systematic analysis of von Willebrand variables, including multimer analysis, PFA-100 and platelet function testing. Awareness of the diagnosis and adequate therapy may help to prevent these patients from bleeding complications in case of surgical interventions or trauma.